Analisis Pengaruh Karakteristik Brand Community Pada Komitmen dan Loyalitas MerekStudi Atas Komunitas Jogja Jazz Club dan Jogja Yaris Community - , Muhammad Rasyid Ridha ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Community is a powerful marketing tool for companies. Because the establishment of brand Community which consists of consumers and potential consumers are a long-term relationships, with the goal providing a real satisfaction from providers of products or services to consumers. In this way, consumers who have used the product brand can have a place to communicate their satisfaction or dissatisfaction to the company. This study tries to to see the influence between the characteristics of brand community, which consists of information quality, system quality, interaction and reward, to community commitment and its relation to brand loyalty. Multiple regression is used as the preferred method analysis. This study is using two community, namely Jogja Jazz Club and Jogja Yaris Community. Respondents who used consists of 60 respondents from Jogja Jazz Club, and 60 respondents from Jogja Yaris Community. The result of analysis shows information quality, system quality, interaction and reward have an influence on community commitment. Futhermore commitment has an influence in increasing brand loyalty.